PREVENTION OF CONGENITAL MALFORMATIONS IN CHILDREN IN UZBEKISTAN: RISK FACTORS ANALYSIS AND RECOMMENDATIONS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
The article examines the current problem of birth of children with congenital developmental defects in the Republic of Uzbekistan. Despite significant achievements in the field of maternal and child health protection, the establishment of perinatal centers, screening laboratories, and genetic counseling centers, the birth rate of children with congenital anomalies remains high, especially in ecologically unfavorable regions and areas with high rates of marriages between relatives. The work analyzes the main causes and risk factors for congenital malformations, including genetic characteristics, adverse environmental factors, vitamin and microelement deficiencies, and insufficient medical monitoring during pregnancy preparation. Special attention was paid to the state programs being implemented in Uzbekistan aimed at preventing congenital pathologies, such as the "Healthy Mother - Healthy Child" program, developing the perinatal screening system, and providing folia to pregnant women. Congenital anomalies represent not only a medical but also a socio-demographic problem, affecting the health level of the population, birth rates, disability structure, and family quality of life. An increased frequency of births of children with developmental defects is observed, first of all, in ecologically unfavorable regions, as well as in those areas where kinship marriages are common. Among the main risk factors, genetic predisposition, exposure to unfavorable environmental conditions, lack of vitamins and microelements, and lack of systematic preparation of women for pregnancy are highlighted. In recent years, Uzbekistan has been implementing state programs aimed at preventing congenital pathologies, particularly the "Healthy Mother - Healthy Child" program, which provides for a set of preventive measures, early diagnosis and screening of pregnant women, providing women with folic acid, and developing the reproductive network.